If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying logx = 2 + -1log(x + -21) Reorder the terms: glox = 2 + -1glo(-21 + x) glox = 2 + (-21 * -1glo + x * -1glo) glox = 2 + (21glo + -1glox) Solving glox = 2 + 21glo + -1glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-21glo' to each side of the equation. -21glo + glox = 2 + 21glo + -21glo + -1glox Combine like terms: 21glo + -21glo = 0 -21glo + glox = 2 + 0 + -1glox -21glo + glox = 2 + -1glox Add 'glox' to each side of the equation. -21glo + glox + glox = 2 + -1glox + glox Combine like terms: glox + glox = 2glox -21glo + 2glox = 2 + -1glox + glox Combine like terms: -1glox + glox = 0 -21glo + 2glox = 2 + 0 -21glo + 2glox = 2 Reorder the terms: -2 + -21glo + 2glox = 2 + -2 Combine like terms: 2 + -2 = 0 -2 + -21glo + 2glox = 0 The solution to this equation could not be determined.
| N^2+18n+38=-7 | | -2(3+6a)=4+2(1-4a) | | -0.8=-0.8u+0.6u | | 5y+3=3y+9 | | 6x-3y+12w-5y-4w+5x= | | 2(2x+7)=56 | | 5w+4y+8x+3x-12y+3w= | | Log(4)(4x)=2 | | 3x^2+48x-780=0 | | 2w+8x+13y+6w+3x-5y= | | -2k-(k-r)+(k-r)+k+(k-(-2k-(k-r)))=63 | | (a^2b^-4)^-5/(7a^2b^-1)-2 | | r+(k-r)+k+(k-r)=63 | | 12n-6(8n+8)=-12(5n-8) | | 30/8 | | (3-z)(3z-2)=0 | | (3n-16)=n^2-6n+3 | | k+(k-r)+2r+(k-r)=63 | | -7(4-8x)-8=-9(x+4)+9x | | 3(2x+4)-8=-2(x+1)+3 | | ((3x^2)/2)-(3x)=0 | | -2(5y+4)+9= | | 2y-2=4y-6 | | 7(n+7)=7(n+6) | | 3K=63+5a | | 16u^4/4u^7 | | (x^2-7x-9)/8 | | k-a+2(k-a-a)=63 | | (X^2-4)^2/3 | | (z-3)/(3z-8) | | 3x+3(-4x+29)=24 | | -9+6p-11p=2(5p-8)+8(4p-5) |